Studi Observasi Hotel Reddoorz Syariah Near Arafah Hospital Jambi - Pratiwi, Heni; Hutabarat, Zuhri Saputra (Jurnal Ekonomi Bisnis Digital, 2024)
RedDoorz is the largest online budget lodging network in Indonesia. Focusing on lodging development and online sales distribution. RedDoorz will select properties that have the potential to collaborate directly and be committed to the RedDoorz brand. RedDoorz helps property owners to improve the quality of their accommodation in terms of facilities and services. The aim of this research is to find out 1. what is the quality of sharia service for guests at the Reddoorz Syariah Hotel near Arafah Hospital Jambi, 2. How management is implemented at the RedDoorz Syariah Hotel near Arafah Hospital Jambi. In the research This is the method used in analyzing the RedDoorz Syariah Hotel using literature review and observation methods to describe and explain the services and facilities at the Syariah Hotel Near Arafah Hospital Jambi. The data used in this research uses primary data obtained directly either through observation or through interviews and also secondary data. The data collection methods in this research are interviews and observations regarding the suitability of halal commitment and management, materials or facilities, sharia accommodation processes, products, as well as monitoring and evaluation of the Reddoorz Syariah Hotel. The results of the study show that the RedDoorz Syariah Hotel Near Arafah Hospital Jambi has implemented The business complies with Islamic law and has MUI halal certification.